ANIMA-LIE: Android-Based Learning Media on Animal Life Cycles Materials for Elementary School - Sri Lestari Handayani; Island Dahlia (Jurnal Ilmiah Sekolah Dasar, 2022)
The learning media used for teachers in online learning during the pandemic are only limited to using pictures, words, sounds, videos, and powerpoints in the form of simple presentations. Thus, the media is not optimal in helping students understand the material and does not increase students' direct experience. It takes the development of online learning media based on android applications to solve these problems. This study aims to develop an android-based learning media "Anima-lie" on animal life cycle material for grade IV elementary school. The research model used is Research and Development (R&D) by applying the ADDIE development model. This application was piloted on 37 fourth grade students. The instrument used is a validation questionnaire for 2 material experts, 2 media experts, and a user response questionnaire. The results of the product developed based on the assessment of material experts get an average score percentage of 85.5% in the good category and for the media expert assessment the average score percentage is 89.93% in the very good category. For the results of student responses, the percentage of the average score is 83.64% with a good category. Based on the data results indicate that the development of the Android-based mobile learning application "Anima-lie" with animal life cycle material is suitable for use as a learning medium for fourth grade elementary school students.